Relationship of Professional Certainty and Organizational Commitment among Teachers - Khan, Tabassum; Imran Bukhari, Syed Muhammad (JISR management and social sciences & economics, 2015)
Present study was designed to explore the relationship of professional certainty and organizational commitment among teachers of Rawalpindi and Islamabad.as a sample 252 teachers were approached in which 205 were females and 47 were males. The data was collected by utilizing self-reported questionnaire. Pearson product moment correlation, linear regression and t-test were applied to perform analysis on the obtained data. Correlation analysis showed a positive relationship exists between professional certainty and organizational commitment. T-test analysis demonstrated insightful contrasts on organizational status, work nature, training and education. Permanent teachers scored higher on organizational commitment than the contractual educators. People who had any training with respect to teaching scored higher on organizational commitment than the people who did not have any such session. Regression analysis on age and experience showed significant positive effect on organizational commitment.